Pengaruh Promosi Penjualan Dan Persediaan Terhadap Keputusan Pembelian Dengan Harga Sebagai Variabel Mediasi Studi Pada Pelanggan Toko “Salah Parkir” Classic Part & Custom Kota Metro - M. Azzam Nurkholis; Suwarto; Ardiansyah Japlani (Universitas Muhammadiyah Metro, 2025)
In order to win the competition, each entrepreneur carries out their own marketing strategy,among the marketing strategies that are generally implemented by each company includeincreasing sales promotions and providing complete stock and types of goods so that buyerswill not move to another shop that has complete stock of goods. Apart from that, settingcompetitive prices is also the key to winning the competition, because price is one of the mainconsiderations for consumers in determining where they will shop. This research aims todetermine the effect of sales promotions and inventory on purchasing decisions with price asa mediating variable for customers of the Classic Part & Custom Part & Custom Shop inMetro City. The research design is quantitative research or verification research. The objectof this research is sales promotion, inventory and purchasing decisions with price as amediating variable. The research population and sample were customers of the